Long‐term evidence that a pediatric oncology mentorship program for young investigators is feasible and beneficial in the cooperative group setting: A report from the Children's Oncology Group. Issue 3 (28th November 2017) - Esbenshade, Adam J.; Pierson, Christopher R.; Thompson, Amanda L.; Reed, Damon; Gupta, Abha; Levy, Adam; Kahalley, Lisa S.; Harker‐Murray, Paul; Schore, Reuven; Muscal, Jodi A.; Embry, Leanne; Maloney, Kelly; et al.
Abstract: Background: Mentorship of junior faculty is an integral component of career development. The Children's Oncology Group (COG) Young Investigator (YI) Committee designed a mentorship program in 2004 whose purpose was to pair YIs (faculty ≤10 years of first academic appointment) with a senior mentor to assist with career development and involvement in COG research activities. This study reports on the committee's ability to achieve these goals. Procedure: An online survey was sent to YIs who were registered with the program from 2004 to2015, assessing three major domains: (1) overall experience with the mentor pairing, (2) satisfaction with the program, and (3) academic accomplishments of the mentees. Results: The response rate was 64% (110/171). Overall, YIs rated the success of their mentorship pairing as 7.2 out of 10 (median) (25th, 75th quartile 3.6, 9.6). The direct effects of the mentorship program included 70% YIs reporting a positive effect on their career, 40% reporting any grant or manuscript resulting from the pairing, 47% forming a new research collaboration, and 43% receiving appointment to a COG committee. Respondents reported success in COG with 38% authoring a manuscript on behalf of COG and 65% reporting a leadership position including seven current or past COG discipline chairs and 20 study chairs. Finally, 74% of respondents said they would consider serving as mentors in the program in the future. Conclusion: The COG YI mentorship program has been well received by the majority of the participants and has helped to identify and train many current leaders in COG.